THE IMPACT OF THE BOARD OF DIRECTORS ON COMPANIES? PERFORMANCE: THE MODERATING ROLE OF OWNERSHIP CONCENTRATION - Hyarat H.I.; Husin N.M.; Jos R.A.G. (Virtus Interpress, 2025)
The impact of the board of directors (BOD) on the performance of companies, particularly considering the moderating role of ownership concentration (OC), is a topic of significant importance in the realm of corporate governance (Habtoor, 2020). The study employs structural equation modelling (SEM), a more advanced method, to address causality and endogeneity issues in governance-performance relationships (Hamid & Purbawangsa, 2022). The hypotheses are constructed based on resource dependence and agency theories, enhancing the theoretical framework. The research focuses on Jordanian service and industrial firms listed on the Amman Stock Exchange (ASE) from 2014 to 2018, encompassing 92 firms and 460 observations. Based on the estimated results, the study confirms that the size of the board, CEO duality, and board independence, including OC, all have a positive effect on firm performance. The results also show that the BOD has a statistically significant impact on firm performance when considering the moderating impact of OC. However, the study finds that CEO duality and board independence have an insignificant impact on return on assets (ROA). This study contributes to the literature on BOD and firm performance and provides insights for practitioners and policymakers. ? 2024 The Authors.